Growth and Yield Performance of Bari Mung-5 Under Different Time of Sowing - Jahan, Nargis; Adam, M M Golam (Journal of Bangladesh Academy of Sciences, 2012)
A field experiment was carried out at University of Dhaka from March to July, 2011 to study the effect of time of sowing on the growth and yield of BARI mung-5. The treatments consisted of three dates of sowing viz. March 15, April 15 and May 15. The crop responded significantly to sowing time and 15 April sowing seeds produced plants having maximum plant height (68.4 cm), leaves/plant (29.33), total dry matter/plant (17.99), branches/plant (8.17), pods/plant (11.33), pod length (8.78 cm), seeds/pod (11.17), 1000 seed weight (46.52 g), seed yield/plant (5.33 g), yield/ha (1.77 t) and harvest index (29.58 %) at harvest. The seed yield decreased by 36.8 and 49.9% when seed sown early (15 March) or late (15 May) due to production of lower yield components. DOI: http://dx.doi.org/10.3329/jbas.v36i2.12966 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 2, 227-231, 2012